Jumanji. Welcome to the jungle [videorecording (Blu-Ray)] - Johnson, Dwayne, 1972-; Black, Jack, 1969-; Hart, Kevin, 1979-; Gillan, Karen, 1987-; Jonas, Nick; Cannavale, Bobby; Van Allsburg, Chris (Sony Pictures Home Entertainment, 2018)
Four high school kids discover an old video game console and are drawn into the game's jungle setting, literally becoming the adult avatars they chose.